Delavaya toxocarpa Franch. - A pioneer species used to reforest the limestone mountains - Tam, Ha Minh; Khoi, Nguyen Khac; Phuong, Vu Xuan (Academia Journal of Biology, 2015)
Delavaya toxocarpa Franch. (Sapindaceae Juss.) is a small tree. This species is a native plant in Vietnam. If scattered in hollow rocks, its seeds can germinate themself and develop very well on the limestone mountains which have not any trees. When they become adult plants, we can intercrop many valuable trees, which establish a reforested model on limestone mountains. This reforested model was constructed in the Phuc Sen commune (Quang Hoa district of Cao Bang province).